Enzymatic hydrolysis of delignified bagasse polysaccharides - Adsul, Mukund G.; Ghule, J. E.; Shaikh, H.; Singh, R.; Bastawade, Kulbhushan B.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2005)
Sugarcane bagasse, consisting of cellulose, xylan, and lignin, was chemically treated to generate bagasse samples with continuously decreasing content of lignin. These bagasse samples were hydrolyzed by cellulase and xylanase enzymes, produced earlier by Penicillium janthinellum NCIM 1171 in the same bagasse polysaccharides production medium. The hydrolysis was carried out by using different concentrations of the enzymes at two different temperatures, 30 and 50 degrees C, taking hydrolysis of Avicel as control. It was found that while the maximum hydrolysis for Avicel was 70% that of some of the bagasse polysaccharides was as high as 95%. The products of hydrolysis were glucose, xylose, and arabinose, as confirmed by high pressure ion chromatography (HPIC). It is interesting to note that arabinose, which constitutes about 10% of the weight of bagasse xylan, could also be released easily by the enzymes. Also, the initial rates of hydrolysis was found to be much higher for the bagasse polysaccharides, and in some cases about 90% of the hydrolysis occurred within 20 h. Amongst all bagasse samples, the sample with (Kappa no. 1.2, lignin content 0.18%) gave the highest degree of hydrolysis at 50 degrees C. Even the bagasse polysaccharide with Kappa no. 16.8 (lignin content 2.5%) underwent greater extent of hydrolysis than Avicel. Apparently, the delignified bagasse medium appears to be a facile medium for the combined hydrolytic action of the cellulase and xylanase enzymes. Considering that sugarcane bagasse is a waste biomass material available in abundance annually, this methodology can be used to value-add to this biomass to produce sugars, which can be fermented to produce biofuels like ethanol. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: bagasse polysaccharides; Cellulase; chemical treatment; Enzymatic hydrolysis; Penicillium janthinellum; Sugarcane bagasse; Xylanase

Purification and properties of a low molecular weight 1,4-beta-D-glucan glucohydrolase having one active site for carboxymethyl cellulose and xylan from an alkalothermophilic Thermomonospora sp - Jagtap, Sharmili; Rao, M (Biochemical and Biophysical Research Communications, 2005)
A low molecular weight 1,4-beta-D-glucan glucohydrolase from an extracellular culture filtrate of Thermomonospora sp. was purified to homogeneity. The molecular weight of the purified enzyme was 14.2 kDa by MALDI-TOF analysis and is in agreement with SDS-PAGE and gel filtration chromatography. The purified enzyme exhibited both endocarboxymethyl cellulase and endoxylanase activities. A kinetic method was employed to study the active site of the enzyme that hydrolyzes both carboxymethyl cellulose and xylan. The experimental data coincide well with the theoretical values calculated for the case of a single active site. Conformation and microenvironment at the active site was probed with fluorescent chemo-affinity labeling using o-phthalaidehyde as the chemical initiator. Formation of isoindole derivative resulted in complete inactivation of the enzyme to hydrolyze both xylan and CMC as judged by fluorescence studies corroborating a single active site for the hydrolysis of xylan and CMC. (C) 2005 Elsevier Inc. All rights reserved.
Keywords: Cellulase; CMC; OPTA; single active site; Thermomonospora sp.; xylan; Xylanase

Application of cellulases from an alkalothermophilic thermomonospora sp in biopolishing of denims - Anish, Ramakrishnan; Rahman, Mohammad Safikur; Rao, Mala (Biotechnology and Bioengineering, 2007)
Use of cellulase for denim washing is a standard eco-friendly technique to achieve desirable appearance and softness for cotton fabrics and denims. But enzymatic washing of denim till date involved acid cellulase (Trichoderma reesei) and neutral cellulase (Humicola isolens) the use of which has a drawback of backstaining of the indigo dye on to the fabric. Though it has been suggested that pH is a major factor in controlling backstaining there are no reports on use of cellulase under alkaline conditions for denim washing. In this study for the first time an alkali stable endoglucanase from alkalothermophilic Thermomonospora sp. (T-EG) has been used for denim biofinishing under alkaline conditions. T-EG is effective in removing hairiness with negligible weight loss and imparting softness to the fabric. Higher abrasive reactivity with lower backstaining was a preferred property for denim biofinishing exhibited by T-EG. The activities were comparable to acid and neutral cellulases that are being regularly used. The enzyme was also effective under non-buffering conditions which is an added advantage for use in textile industry. A probable mechanism of enzymatic finishing of cotton fabric has been represented based on the unique properties of T-EG.
Keywords: alkaline conditions; biopolishing; Cellulase; denim; Thermomonospora sp

Fluorescence study on interactions of alpha-crystallin with the molten globule state of 1, 4-beta-D-glucan glucanohydrolase from thermomonospora sp induced by guanidine hydrochloride - Jagtap, Sharmili; Rao, Mala (Journal of Fluorescence, 2009)
In this paper, the interaction between alpha- crystallin and molten globule structure of 1,4-beta-D-Glucan Glucohydrolase (TSC) from an alkalothermophilic Thermomonospora sp. was investigated mainly by fluorescence quenching spectra, circular dichroism and three dimensional fluorescence spectra under simulative physiological conditions. Denaturation studies using GdnCl indicated that TSC folds through a partially folded state that resembles molten globule at 1.8 M GdnCl. The chaperone activity of alpha- crystallin was employed to study refolding of TSC. Here we studied the refolding of GdnCl denatured TSC from its molten globule state (TSC-m complex) in the presence and absence of alpha-crystallin to elucidate the molecular mechanism of chaperone-mediated in vitro folding. Our results, based on intrinsic tryptophan fluorescence and ANS binding studies, suggest that alpha-crystallin formed a complex with a putative intermediate molten globule - like intermediate in the refolding pathway of TSC. Reconstitution of the active TSC was observed on cooling the alpha-crystallin aEuro cent TSC -m complex to 4A degrees C. Addition of alpha-crystallin to the molten globule - like intermediate of TSC (TSC-m complex) complex initiated the refolding of TSC with 69 % recovery of the biological activity of the enzyme.
Keywords: ANS; Cellulase; Guanidine hydrochloride; Protein folding

Enhanced enzymatic hydrolysis of cellulose by partial modification of its chemical structure - Shaikh, H. M.; Adsul, Mukund G.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2011)
A series of 2,3-dialdehyde celluloses with different degrees of oxidation were used for deriving corresponding dicarboxylate, dicarboxy, and Schiff's base cellulose derivatives. The dialdehyde cellulose was hydrolyzed by cellulase to a lower extent than the starting cellulose, except at high levels of aldehyde content (above 50%). For dicarboxylate and dicarboxy celluloses, the highest level of oxidized NaDCC and DCC hydrolysed up to 70 and 60% respectively which was 3-4 times more than cellulose. The 2,3-dioxime cellulose derivative hydrolyzes only up to 16.3% for the highest level of oxidized dioxime. In the case of 2,3-diethylimine cellulose, all derivatives hydrolyse faster than the native cellulose. Up to 75% hydrolysis was observed for 2,3-diethyimine cellulose-50, 2,3-dipropylimine and 2,3-dibutylimine cellulose. The 2,3-dibenzylimine cellulose hydrolyses a little slower than the alkylimine derivatives. The 2,3-dihydrazone cellulose derivatives with all level of oxidation showed resistance towards enzymatic hydrolysis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 2; 3-Dialdehyde celluloses; 3-Dibenzylimine cellulose; 3-Dibutylimine cellulose; 3-Dicarboxy celluloses; 3-Diethyimine cellulose; 3-Dihydrazone cellulose; 3-Dipropylimine cellulose; Cellulase; Enzymatic hydrolysis

Bacillus cellulasensis sp nov., isolated from marine sediment - Mawlankar, Rahul R.; Thorat, Meghana N.; Krishnamurthi, Srinivasan; Dastager, Syed Gulam (Archives of Microbiology, 2016)
A novel bacterial strain NIO-1130(T) was isolated from sediment sample taken from Chorao Island, Goa Province, India, and subjected to a taxonomic investigation. The strain was Gram-positive, aerobic, and motile. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and strain NIO-1130(T) showed highest sequence similarity with Bacillus halosaccharovorans DSM 25387(T) (98.4 %) and Bacillus niabensis CIP 109816(T) (98.1 %), whereas other Bacillus species showed < 97.0 % similarity. Tree based on gyrB gene sequence revealed that strain bacillus group. The major menaquinone was MK-7 and the predominant cellular fatty acids were iso-C-15:0, anteiso-C-15:0, iso-C-17:0, and anteiso-C-17:0. The strain showed a DNA G+C content of 39.9 mol%. DNA-DNA hybridization studies revealed that strain NIO-1130(T) exhibits 70 % similarity with Bacillus halosaccharovorans DSM 25387(T) and Bacillus niabensis CIP 109816T. On the basis of physiological, biochemical, chemotaxonomic and phylogenetic analyses, we consider the isolate to represent a novel species of the genus Bacillus, for which the name Bacillus cellulasensis sp. nov., is proposed. The type strain is NIO-1130(T) (=NCIM 5461(T) = CCTCC AB 2011126(T)).
Keywords: Bacillus sp; Cellulase; Marine sediment; Polyphasic taxonomy

Penicillium janthinellum NCIM1366 shows improved biomass hydrolysis and a larger number of CAZymes with higher induction levels over Trichoderma reesei RUT-C30 - Sreeja-Raju, Athiraraj; Christopher, Meera; Kooloth-Valappil, Prajeesh; Kuni-Parambil, Rajasree; Gokhale, Digambar Vittal; Sankar, Meena; Abraham, Amith; Pandey, Ashok; Sukumaran, Rajeev K. (Biotechnology for Biofuels, 2020)
Background Major cost of bioethanol is attributed to enzymes employed in biomass hydrolysis. Biomass hydrolyzing enzymes are predominantly produced from the hyper-cellulolytic mutant filamentous fungus Trichoderma reesei RUT-C30. Several decades of research have failed to provide an industrial grade organism other than T. reesei, capable of producing higher titers of an effective synergistic biomass hydrolyzing enzyme cocktail. Penicillium janthinellum NCIM1366 was reported as a cellulase hyper producer and a potential alternative to T. reesei, but a comparison of their hydrolytic performance was seldom attempted. Results Hydrolysis of acid or alkali-pretreated rice straw using cellulase enzyme preparations from P. janthinellum and T. reesei indicated 37 and 43% higher glucose release, respectively, with P. janthinellum enzymes. A comparison of these fungi with respect to their secreted enzymes indicated that the crude enzyme preparation from P. janthinellum showed 28% higher overall cellulase activity. It also had an exceptional tenfold higher beta-glucosidase activity compared to that of T. reesei, leading to a lower cellobiose accumulation and thus alleviating the feedback inhibition. P. janthinellum secreted more number of proteins to the extracellular medium whose total concentration was 1.8-fold higher than T. reesei. Secretome analyses of the two fungi revealed higher number of CAZymes and a higher relative abundance of cellulases upon cellulose induction in the fungus. Conclusions The results revealed the ability of P. janthinellum for efficient biomass degradation through hyper cellulase production, and it outperformed the established industrial cellulase producer T. reesei in the hydrolysis experiments. A higher level of induction, larger number of secreted CAZymes and a high relative proportion of BGL to cellulases indicate the possible reasons for its performance advantage in biomass hydrolysis.
Keywords: Bioethanol; CAZymes; Cellulase; Penicillium janthinellum; Secretome; Trichoderma reesei

Lignocellulose degradation by Penicillium janthinellum enzymes is influenced by its variable secretome and a unique set of feedstock characteristics - Christopher, Meera; Sreeja-Raju, Athiraraj; Sankar, Meena; Gokhale, Digambar Vitthal; Pandey, Ashok; Sukumaran, Rajeev K. (Bioresource Technology, 2022)
Substrate characteristics and proteins that affect lignocellulose-hydrolysis by the hypercellulolytic fungus Peni-cillium janthinellum NCIM 1366 (PJ-1366) were investigated. The hydrolysis rate of PJ-1366 enzymes was very high, with upto 75 % of the reaction being completed in initial 4 h. Comparison of the hydrolytic efficiencies on differently pretreated biomass indicated that the greatest (negative) effect was imparted by lignin, suggesting that improving ligninase activity of the PJ-1366 enzymes may help to improve hydrolysis. Larger pore sizes and higher crystallinity of substrates, which favor enzyme penetration and processive hydrolysis, positively influ-enced hydrolysis efficiency. For alkali-pretreated substrates, 16 FPU/g of PJ-1366 cellulases released the sugar -equivalent of using 10 FPU/g of a commercial biomass hydrolyzing enzyme. By correlation analysis, 41 proteins, including 20 CAZymes were identified, whose abundance in the secretome positively correlated with the cellulase activities of the culture filtrate. These proteins may be considered as the primary drivers of FPase/ CMCase/pNPGase/xylanase activity in PJ-1366.
Keywords: Biofuel; CAZyme; Cellulase; Penicillium; Secretome

Cellulase hyper-producing fungus penicillium janthinellum NCIM 1366 elaborates a wider array of proteins involved in transport and secretion, potentially enabling a diverse substrate range - Christopher, Meera; Sreeja-Raju, Athiraraj; Kooloth-Valappil, Prajeesh; Gokhale, Digambar Vitthal; Sukumaran, Rajeev K. (Bioenergy Research, 2023)
The efficient breakdown of lignocellulose requires the concerted activity of multiple enzymes. Previous studies on Penicillium janthinellum NCIM 1366 (PJ-1366) have revealed a more versatile repertoire of cellulases as compared to the hypercellulolytic strain Trichoderma reesei RUT-C30. Since a robust transport and secretion network is necessary to achieve proficient enzyme production, the transporters and extracellular proteins of PJ-1366 identified from its genome data were compared with those of Penicillium rolfsii (the phylogenetically closest species) and T. reesei RUT-C30 (the industrial work horse for cellulase production). Transmembrane proteins formed 20.4%, 21.0% and 18.2%, respectively of the proteome of PJ-1366, P. rolfsii and T. reesei RUT-C30, and 292 of them were mapped as transporters in PJ-1366. Major facilitator superfamily transporters (264) and sugar transporters (167) are abundant in PJ-1366, which probably aid in the uptake of oligosaccharide inducers of cellulase. The number of extracellular proteins (1007) in PJ-1366 is the highest reported for a Penicillium species. Also, PJ-1366 encoded 1.5 x more proteins involved in carbohydrate metabolism than the other fungi, and its secreted CAZymes belonged to much more diverse families (73), potentially enabling the fungus to act on heterogenous substrates. Structural differences in some untranslated protein response (UPR) effectors like Pdi and Clx detected in PJ-1366 may facilitate unique modes of cellulase regulation.
Keywords: Cellulase; Pathway; Penicillium; regulation; Secretion; Transport

Comparison of the solid-state and submerged fermentation derived secretomes of hyper-cellulolytic Penicillium janthinellum NCIM 1366 reveals the changes responsible for differences in hydrolytic performance - Sankar, Meena; Mathew, Reshma M.; Puthiyamadam, Anoop; Sreeja-Raju, Athiraraj; Christopher, Meera; Gokhale, Digambar Vitthal; Sukumaran, Rajeev K. (Bioresource Technology, 2023)
better hydrolytic performance along with a higher initial rate of reaction. Secretome analyses of the SSF and SmF enzymes using LC/MS-MS, indicated that while the type of proteins secreted were similar in both modes, the abundance of specific beta glucosidases, lytic polysaccharide monooxygenases and hemicellulolytic enzymes were very high in SSF resulting in efficient initiation, low accumulation of cellobiose and high initial reaction rates. Key enzymes that catalyse lignocellulose breakdown under SSF and SmF are therefore different and the fungus may be speculated to have regulation mechanisms that aid differential expression under different culti
Keywords: Cellulase; Solid -state fermentation

Bioprocess optimization of penicillium funiculosum NCIM 1228 for improved production and hydrolytic efficiency of cellulases on sugarcane bagasse - Chavan, Sambhaji B.; Shete, Ashvini M.; Dharne, Mahesh S. (Sugar Tech, 2024)
The cellulase enzyme is currently the world's third largest commercial enzyme. Because of its requirement in various industries like textiles, food, waste management, pharmaceuticals, agriculture, pulp paper, biofuels, and others, its demand curve has increased sharply. The response surface methodology (RSM) approach was employed to optimize media components and process parameters in the current investigation, which successfully increased the cellulase production from Penicillium funiculosum NCIM 1228. Statistical optimization for the hyperproduction of cellulases was conducted using RSM. The Plackett-Burman design (PBD) approach was used to investigate the critical factors of the cellulase production medium. Subsequently, the Box-Behnken design (BBD) method was used to statistically estimate optimum values and conditions that substantially impacted cellulase production. The estimated optimal combinations of parameters for cellulase production were urea (0.2%), CaCl2 (0.2%), MgSO4 (0.05%), peptone (1.5%), microcrystalline cellulose (5.0%), wheat bran (2.5%), corn steep liquor (CSL) (2.5%), KH2PO4 (0.15%), inoculum (10.65%), agitation (157 rpm), pH (5.88), and temperature (29.84 C-degrees). Conclusively, experimental validation under optimal conditions detected an increased production of 3.82- and 3.61-fold in filter paper assay (FPase) and beta-glucosidase, respectively. Additionally, 1.66- and 1.57-fold enhancement in FPase and beta-glucosidase specific activity was observed where an xylanase activity was enhanced by 3.29-fold. Furthermore, the enzyme showed 51.30 per cent hydrolysis efficiency on sugarcane bagasse lignocellulosic biomass (LCB), at a dose of 7 FPase units per g of cellulose. P. funiculosum NCIM 1228 offers the benefit of producing cellulase with an entire cellulolytic system of enzymes that can be synthesized extracellularly, thus acting as a promising biocatalyst for biofuel industries.
Keywords: Cellulase; Lignocellulosic biomass; Penicillium funiculosum; Response surface methodology; Submerged fermentation; Xylanase